Design of concrete fracture property by average aggregate size. (September 2021) - Chen, Yi; Han, Xiangyu; Hu, Xiaozhi; Li, Qingbin
Abstract: This study presents a design methodology for concrete fracture properties, linking the average aggregate size d av to the tensile strength f t and fracture toughness K IC for a given cement grade and water/cement (W/C) ratio. Two different concrete mixes with d av  = 3.5 and 7 mm were tested and analyzed. Similar peak load P max values were obtained under three-point-bending conditions, but with different "ductility". Variations of f t & K IC with d av were established by a simple design formula, which can be used to tailor bulk concrete fracture properties for specific purposes. A statistical method was introduced to estimate the effective d av if only the maximum aggregate size d max was given. Comprehensive fracture data in literature were analyzed to demonstrate the estimation of d av from d max . The purposely designed concrete mixes and data in literature show the significance of d av design even after the cement grade and W/C ratio are fixed. Highlights: A design method is proposed to consider the average aggregate d av besides W/C ratio and cement grade. Designed two concrete mixes with similar load bearing capacity, but different strength and toughness properties. Concrete fracture properties can be tailored using a simple closed-form formula for specified requirements. The equivalent d av for a concrete mix can be statistically estimated even if only from the maximum aggregate d max is known. Experimental scatters can be modelled, and the reliability range can be specified statistically.